A Systematic Review of Nurse Station Performance at Outpatient Room in Hospital - Yetti, Aprodita Emma; Fitria, Tika Ainunnisa (Departement of Architecture, Universitas Islam Indonesia, 2025)
The outpatient area is important in the hospital because it provides care and services to patients with complex and high-standard operational flows. Medical personnel must be able to work according to professional, operational, and service standards. The factors considered are the accuracy and speed of service to patients. For this reason, the layout of the nurse station used by medical personnel plays an important role in the patient service process. This study uses a qualitative method with an inductive-descriptive discussion. Data were obtained through literature studies. The results of the literature study are variables that can be developed for further research, which are also the objectives of this study. The study's results explain the relationship between the effectiveness of the nurse station layout in the outpatient area and the performance of medical personnel. It can enrich existing theories and become recommendations for arranging the layout of nurse stations in hospitals.